2011
DOI: 10.1094/phyto-11-10-0317
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Molecular Make-Up of the Potato virus Y Strain PVYZ: Genetic Typing of PVYZ-NTN

Abstract: Potato virus Y (PVY) strains were originally defined by interactions with different resistance genes in standard potato cultivars. Five distinct strain groups are defined that cause local or systemic hypersensitive responses (HRs) in genetic background with a corresponding N gene: PVY(O), PVY(N), PVY(C), PVY(Z), and PVY(E). The nucleotide sequences of multiple isolates of PVY(O) and PVY(N) differ from each other by ≈8% along their genomes. Additionally, complete genome sequences of multiple recombinant isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(34 citation statements)
references
References 53 publications
(61 reference statements)
1
33
0
Order By: Relevance
“…Subsequent biological characterization of PVY NTN isolates on cvs. Desiree and King Edward showed induced systemic tuber necrosis (Kerlan et al, 2011). Baldauf et al (2006) found PVY NTN to cause ringspot necrosis of potato tubers, while PVY O , PVY C , PVY N and PVY N:O did not.…”
Section: Resultsmentioning
confidence: 98%
“…Subsequent biological characterization of PVY NTN isolates on cvs. Desiree and King Edward showed induced systemic tuber necrosis (Kerlan et al, 2011). Baldauf et al (2006) found PVY NTN to cause ringspot necrosis of potato tubers, while PVY O , PVY C , PVY N and PVY N:O did not.…”
Section: Resultsmentioning
confidence: 98%
“…However, due to a single nucleotide change at nucleotide 1627 (A to G), resulting in a single amino acid change (D to G) in the HC-Pro, this isolate does not cause vein necrosis in tobacco. Therefore, it was later assigned to PVY Z by Kerlan et al (2011).…”
Section: Discussionmentioning
confidence: 99%
“…However, some of these tuber necrotic symptoms were reported to be atypical as they were roughly circular, sunken necrotic lesions on the surface of the potato tuber instead of the typical external ring pattern of PTNRD symptoms (Piche et al, 2004). The ability to induce tuber necrosis on Yukon Gold was also reported for NE-11, PVY-L26 and PVY-MON isolates, the only representatives for PVY-NE11, PVY Z and PVY E groups, respectively (Piche et al, 2004;Lorenzen et al, 2008;Kerlan et al, 2011;Galvino-Costa et al, 2012). Actually, it has been proposed that all PVY N isolates are able, under appropriate growing conditions, to induce necrosis on potato tubers (Kerlan and Tribodet, 1996).…”
Section: Introductionmentioning
confidence: 95%